2018
DOI: 10.1149/2.1271809jes
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Capacitance Properties of Nanocrystalline MnCO3by the Effect of a Carbonizing Agent

Abstract: Nanocrystalline MnCO 3 is synthesized by hydrothermal reduction of KMnO 4 using different amounts of pyrrole. The effect of molar ratio of KMnO 4 :pyrrole on the phase purity, size of the particle, textural and capacitance properties of MnCO 3 is studied systematically using various physico-chemical and electrochemical techniques. While X-ray diffraction studies confirm decline in the phase purity of MnCO 3 , FTIR, Raman spectroscopic and thermogravimetric studies reveal an increase in the amount of adsorbed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The R s and R ct were computed by fitting impedance spectra using an equivalent circuit shown in Figure c. It is well known that poor cycling stability of the electrode material is attributed to instability of the material causing phase change or dissolution during cycling, increase in the internal resistance of the material, etc ,. Owing to the high chemical and structural stability of MGCN, it neither undergone dissolution nor phase change during extended cycling as reflected in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…The R s and R ct were computed by fitting impedance spectra using an equivalent circuit shown in Figure c. It is well known that poor cycling stability of the electrode material is attributed to instability of the material causing phase change or dissolution during cycling, increase in the internal resistance of the material, etc ,. Owing to the high chemical and structural stability of MGCN, it neither undergone dissolution nor phase change during extended cycling as reflected in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some of the metal oxides undergo phase transformation during extended GCD cycling . Nevertheless, MnCO 3 retains its phase even after 500 GCD cycles in aqueous 0.1 M Mg(ClO 4 ) 2 electrolyte (Figure d) …”
Section: Resultsmentioning
confidence: 93%
“…In addition, it also exhibits electrochromism . Most importantly, MnCO 3 is studied extensively as an anode material in lithium‐ion batteries, and as an electroactive material in supercapacitors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly studied materials include metal oxides or metal hydroxides such as RuO 2 , MnO 2 , Co 3 O 4 , Ni­(OH) 2 , and Co­(OH) 2 . Although these compounds provide significantly higher theoretical capacitance than carbon materials, their actual performance generally suffers due to poor conductivity and stability. As such, alternative pseudocapacitor materials with improved properties are continuously being sought after, MnCO 3 being one of them. Various methods have been used to synthesize MnCO 3 nanostructures with different morphologies and compositions. For example, micron-sized spheres comprised of agglomerated submicron MnCO 3 cubes were prepared by electrodeposition from an aqueous mixture of MnSO 4 and Na 3 C 6 H 5 O 7 .…”
Section: Introductionmentioning
confidence: 99%